DEVELOPING READING SKILLS THROUGH DIFFERENT FORMS OF ASSESSMENT - Rasulova Sokhiba Azizjon qizi (Western European Studies, 2025)
Reading skills are essential for academic and cognitive development, and effective assessment plays a key role in enhancing these skills. This article explores how different forms of assessment, including formative, summative, diagnostic, and authentic assessments, contribute to the development of reading proficiency. The review incorporates perspectives from multiple researchers, such as Black and Wiliam (1998), Hattie and Timperley (2007), Snow (2010), and Wiggins (1990), who have explored the impact of assessment practices on literacy development. By examining the benefits and limitations of each assessment type, this article highlights how these tools can be used strategically to support diverse learners and improve reading skills across various contexts. A balanced approach to assessment is essential for fostering a comprehensive understanding of reading proficiency and facilitating continuous improvement in students' reading development
Keywords: reading skills; formative assessment; summative assessment